Решите уравнение:
10(х+1)2 – (3х-1)2=(х+4)(х-4)

del9832 del9832    2   09.04.2022 11:04    0

Ответы
sasacot sasacot  09.04.2022 11:10

10(х+1)2-(3х-1)2 = (х+4)(х-4)

20(х+1) - (3х-1)2 = х²-16

20х+20 - 6х+2= х²-16

20х+20-6х+2-х²+16=0

-х²+20х-6х+20+2+16=0

-х²+14х+38=0 / (-1)

х²-14х-38=0

√Д= √14²-4*(-38) = √196+152 = √348

х1х2= 14±√348/2 = 14±2√87/2 (тут мы 348 разделили на две части, а именно 4×87 и из 4 взяли корень) = 7±√87

ответ: 7±√87

ПОКАЗАТЬ ОТВЕТЫ
dima19820325 dima19820325  09.04.2022 11:10

ответ:
7±√87

Объяснение:

я запарился это решать

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра